Identifikasi Persepsi Konsumsi Minuman Keras di Kalangan Mahasiswa Strata 1 UIN Sunan Kalijaga Yogyakarta - Tasya Alivia; Atika Nada Sari; Rezky Aryani; Nanda Dwi Febriyanti; Dhea Aisyah Rahma; Huri Dewi Rizkiyatul Amaliyah (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2025)
Liquor has a harmful impact on individuals who consume it continuously and on the social community in the environment of individuals who consume it. One of them can be seen during the stabbing case that occurred in Yogyakarta, as well as research that states the many adverse effects of consuming alcohol on students. This study aims to determine UIN Sunan Kalijaga undergraduate students' perceptions of students who consume alcohol. This research uses the Situational Theory of Public (STP). This research uses quantitative research methods, data collection techniques, questionnaires for 100 samples, and data analysis using statistical tests and the Respondent Achievement Rate (TCR). This study shows the results that undergraduate students of UIN Sunan Kalijaga do not have an understanding and do not care about the problems or issues related to consuming alcohol among students. This is indicated by the average TCR result of 42.87% of the four sub-variables used in this study. Keywords: Perception Identification, Situational Theory of Public, Students, Liquor, Respondent Achievement Rate